Explanation People and Their Family Care Explanation of Them - Sharareh Farzanegan; Reza Fadaye Vatan; Mahboube Mobasheri; Reza Seraj; Yazdan Mansourian (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Elder abuse (Doing or not done a single or repeated act That bothers or to cause harm to an elderly) is one of the social health problems in modern societies to rise and has a prominent role in prevention education The objective of this study was to investigate elderly abuse in Persian literature. Methods & Materials: This study identified themes related to elder abuse in Persian literature and the educational structure were developed developed In this regard, poems of poets and authors of Persian literature Using the software for Dorj book including 178 of 101 literary Persian poet and author is known and ganjur Site including large number of poets and In cases where there was no electronic versions of books were read line by line And using a library of content analysis, subjects were studied Results: The study defined types of elder abuse and elder abuse causes of elder abuse and how to prevent abuse of the elderly that each expression is detailed in the text Conclusion: The results of the rich Persian literature could result in abuse of elderly has been considered from two aspects 1- denounced the abuse of older 2- culture of reverence and respect for the elderly in order to prevent abuse of the elderly